‘Wino z jęczmienia’ – właściwości piwa antycznego w świetle literatury greckiej i rzymskiej - Wojciech Duszyński (In Gremium. Studies in History, Culture and Politics, 2025)
The article deals with the perception of a beer among Greeks and Romans. It is being argued, that a common view, about their critical stance towards the beverage, requires correction. Some passages in classical literature demonstrate rather positive evaluation of beer by the ancients. The text focuses on remarks about various sensual experiences, that our sources associate with ancient beer (or beers). These passages are juxtaposed with a modern knowledge about beer production and its biochemical conditions. The analysis allows us to put forward a thesis, that ancient beers could have been similar to grape (fruit) wines, in some respects. This is reflected in the ancient literature, where the term ‘barley wine’ (οἶνος κρίθινος) appears several times. The negative attitude towards beer may reflect the optics of higher social strata, that most of the available sources comes from. Moreover, the complexity of beer’s production process (in comparison with wine) could have played an important role in shaping of opinions among ancient people. It was easy then to compare ‘bad’ (spoiled) beer with ‘good’ (unspoiled) wine.